Polyacrylonitrile fiber composite adsorption material and preparation method and application thereof

CN122828703BActive Publication Date: 2026-10-30ANHUI POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611349692.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30
Estimated Expiration
2046-09-02

AI Technical Summary

Technical Problem

现有技术中通常关注其作为吸附填料或导电填料的作用,但在海藻酸钠/HKUST-1/聚丙烯腈纤维复合吸附体系中,如何将炭黑稳定固定在Cu²+交联海藻酸钠凝胶层中,并利用炭黑调节HKUST-1在纤维表面的成核和生长,同时赋予材料稳定光热响应和光热辅助吸附去除能力,仍缺少针对性的结构设计

Benefits of technology

1.本发明通过氧化锌辅助HKUST-1在室温条件下原位生成,在聚丙烯腈纤维表面构建海藻酸钠/炭黑/HKUST-1复合吸附层,提高材料在水相中的润湿性能、传质效率和吸附位点利用率,同时赋予材料光热响应能力。其中,炭黑在作为吸附材料的同时,还参与调节HKUST-1生长和界面传质过程,使材料在光照条件下表现出更快的吸附去除速率;具体而言,炭黑固定在海藻酸钠凝胶层中后,一方面为HKUST-1在纤维表面原位生长提供粗糙复合界面以及更多的成核和生长位置,并形成含HKUST-1的复合覆盖层;另一方面使复合吸附材料具有光热响应。此外,由于炭黑的引入增强了材料的光热响应,该光热响应可能是影响光照条件下盐酸四环素去除过程的因素之一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122828703B_ABST
    Figure CN122828703B_ABST
Patent Text Reader

Abstract

The present application relates to the technical fields of environmental functional materials and water treatment adsorption materials, and discloses a polyacrylonitrile fiber composite adsorption material, a preparation method and application thereof. Zinc oxide, carbon black and sodium alginate are placed in water to obtain a SA / CB / ZnO water dispersion, and then polyacrylonitrile fibers are coated with the SA / CB / ZnO water dispersion, crosslinked with copper ions, and then placed in a trimesic acid solution to generate HKUST-1 in situ, thereby obtaining a polyacrylonitrile fiber composite adsorption material. The zinc oxide is used to assist the in-situ generation of HKUST-1 at room temperature, the carbon black is used to adjust the growth of HKUST-1 and the interface mass transfer process, and the carbon black is used as an adsorption material and makes the material exhibit a faster adsorption removal rate under light conditions. The composite adsorption material has a fibrous macroscopic morphology, water phase wetting performance, tetracycline hydrochloride removal capacity and photothermal response, is convenient to recycle and reuse, and can be used for antibiotic wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental functional materials and water treatment adsorption materials, specifically to a polyacrylonitrile fiber composite adsorption material, its preparation method, and its application. Background Technology

[0002] In the treatment of antibiotic-contaminated water, common adsorbent materials such as activated carbon, biochar, resin, clay minerals, and polymer adsorbents often suffer from slow adsorption rates, insufficient utilization of effective adsorption sites, and unsatisfactory cycle stability. The main reasons for this are insufficient surface wettability, limited pore accessibility, or a small number of surface functional groups, making it difficult for tetracycline hydrochloride molecules to migrate rapidly to internal adsorption sites.

[0003] To address the challenge of recycling powdered metal-organic frameworks (MOFs), existing technologies include loading MOFs onto membranes, particles, sponges, gels, or fiber supports. While these immobilized structures improve the macroscopic separability of the materials, they still suffer from drawbacks such as unstable loading, uneven crystal distribution, and coverage of adsorption sites [Fang SY, Zhang P, Gong JL, et al. Chemical Engineering Journal, 2020, 385: 123400.]. When using simple dip coating or physical mixing methods, the binding force between MOF crystals and the support is weak, and they are prone to detachment during adsorption, rinsing, and regeneration [Zhan Y, He S, Hu J, et al. Journal of hazardous materials, 2020, 388:121752.]. When using dense polymer coating, the coating layer may block MOF pores or block metal active sites, affecting the entry of tetracycline hydrochloride into the internal pores [Ye H, Chen D, Li N, et al. Journal of Membrane Science,2021, 637: 119619.]. Some support surfaces are relatively flat and lack sufficient nucleation and fixation sites, making it easy for MOF crystals to accumulate locally, which is not conducive to mass transfer and site exposure.

[0004] HKUST-1, also known as CuBTC or MOF-199, is a copper-based metal-organic framework material with a well-defined crystal structure and abundant porosity. Copper nodes and organic ligands provide adsorption sites for tetracycline hydrochloride. While loading a sodium alginate / HKUST-1 composite layer solely onto the surface of polyacrylonitrile fibers can improve HKUST-1 recovery, there is still room for improvement in fiber surface roughness, wetting rate, HKUST-1 crystal growth density, and interfacial mass transfer capacity. During antibiotic adsorption and removal, tetracycline hydrochloride molecules need to first fully contact the composite adsorption layer on the fiber surface before diffusing to the outer surface of the HKUST-1 crystals, pore entrances, copper nodes, and organic ligand sites. If the composite layer wets slowly, the HKUST-1 growth is insufficient, or the mass transfer resistance is high, the effective adsorption sites on the material surface cannot be fully utilized.

[0005] Carbon black is a common carbon material with strong light absorption and a certain degree of surface roughness. Current technologies typically focus on its role as an adsorbent or conductive filler, but in the sodium alginate / HKUST-1 / polyacrylonitrile fiber composite adsorption system, how to stably fix carbon black on Cu²⁺ is a key challenge. + While cross-linking sodium alginate gel layers and utilizing carbon black to regulate the nucleation and growth of HKUST-1 on the fiber surface, thereby endowing the material with stable photothermal response and photothermal-assisted adsorption and removal capabilities, targeted structural designs are still lacking. For carbon materials such as carbon nanotubes and graphene, which possess light absorption and photothermal conversion capabilities, targeted structural designs are needed to ensure their stable immobilization within sodium alginate gel layers and to regulate the nucleation and growth of HKUST-1 and interfacial mass transfer.

[0006] Therefore, existing technologies still require a polyacrylonitrile fiber composite adsorbent material that is stable in load, rapidly wettable, easy to recycle, and reusable. This material should not only reduce the agglomeration and loss of powdered HKUST-1, but also form a composite interface on the fiber surface conducive to the in-situ growth of HKUST-1. Furthermore, it should improve the overall removal rate of tetracycline hydrochloride under light conditions. Moreover, under the coexistence of light and hydrogen peroxide, it should utilize copper-containing sites in the material to promote the oxidation reaction of hydrogen peroxide, achieving synergistic removal through adsorption and Fenton-like catalytic oxidation, thereby improving the removal efficiency of antibiotic pollutants. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide a polyacrylonitrile fiber composite adsorption material, its preparation method, and its application.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a polyacrylonitrile fiber composite adsorbent material includes the following steps: Zinc oxide and carbon black were dispersed in water, and sodium alginate was added and mixed evenly to obtain an SA / CB / ZnO aqueous dispersion. Polyacrylonitrile fibers were coated with SA / CB / ZnO aqueous dispersion, then transferred to copper nitrate aqueous solution for ionic crosslinking reaction, and then placed in pyromellitic acid solution to generate HKUST-1 in situ, thus obtaining polyacrylonitrile fiber composite adsorbent material.

[0009] In the above steps, HKUST-1 is generated in situ at room temperature with the assistance of zinc oxide, constructing a sodium alginate / carbon black / HKUST-1 composite adsorption layer on the surface of polyacrylonitrile fibers. This improves the wettability, mass transfer efficiency, and adsorption site utilization of the polyacrylonitrile fiber composite adsorption material in the aqueous phase, while also endowing the material with photothermal response capabilities. Carbon black, while acting as an adsorption material, also participates in regulating the growth of HKUST-1 and the interfacial mass transfer process, enabling the material to exhibit a faster adsorption and removal rate under light conditions. Specifically, after carbon black is fixed in the sodium alginate gel layer, it provides a rough composite interface and more nucleation and growth sites for the in-situ growth of HKUST-1 on the fiber surface, forming a composite coating layer containing HKUST-1. On the other hand, it gives the composite adsorption material photothermal response.

[0010] Preferably, in the SA / CB / ZnO aqueous dispersion, the ratio of zinc oxide, carbon black, sodium alginate, and water is (0.2-0.48g):(0.4-0.72g):(1-1.8g):(50-60mL).

[0011] Preferably, the preparation process of the copper nitrate aqueous solution includes the following steps: dissolving 1-2g of copper nitrate trihydrate in 50mL of deionized water, ultrasonicating until completely dissolved, and then magnetically stirring for 15min.

[0012] Preferably, in the preparation of the copper nitrate aqueous solution, the concentration of copper nitrate trihydrate is 20.0-40.0 mg / mL, based on the volume of water used for solution preparation.

[0013] Preferably, the preparation process of the pyromellitic acid solution includes the following steps: dissolving 2.88-3.84g of pyromellitic acid in 64mL of anhydrous ethanol, then adding 64mL of N,N-dimethylformamide and 64mL of deionized water, and stirring until completely dissolved.

[0014] Preferably, in the pyromellitic acid solution, the concentration of pyromellitic acid is 15.0-20.0 mg / mL, calculated as the sum of the volumes of the three solvents added: ethanol, N,N-dimethylformamide, and water.

[0015] Preferably, the specific process of the coating treatment includes the following steps: immersing polyacrylonitrile fibers in an SA / CB / ZnO aqueous dispersion and performing multiple continuous immersions at a temperature of 25°C, with each immersion lasting 2-5 minutes, to obtain SA / CB / ZnO / PAN coated fibers after the immersion is completed.

[0016] Furthermore, the multiple consecutive impregnations refer to the process where, after the previous impregnation, the fiber is removed without drying and immediately impregnated in the original impregnation solution (i.e., the impregnation solution of the previous impregnation) for the next impregnation, and so on for a total of 2-4 impregnations.

[0017] Preferably, the specific process of the ionic crosslinking reaction includes the following steps: transferring the coated polyacrylonitrile fiber into a copper nitrate aqueous solution, immersing it at 25°C for 10-20 minutes to carry out the ionic crosslinking reaction, removing it after crosslinking, and washing it with deionized water to remove free copper ions and nitrate ions that did not participate in crosslinking on the surface.

[0018] Preferably, the specific process for in-situ generation of HKUST-1 includes the following steps: placing polyacrylonitrile fibers that have undergone coating treatment and ion crosslinking reaction in a pyromellitic acid solution and reacting at 25°C for 30-50 minutes to generate HKUST-1 in situ; after the reaction is completed, removing the fibers and washing them alternately with anhydrous ethanol and deionized water, and then vacuum drying them.

[0019] Preferably, the ratio of the polyacrylonitrile fiber, SA / CB / ZnO aqueous dispersion, copper nitrate aqueous solution, and trimesic acid solution is 1g:(150-200mL):(150-200mL):(150-200mL).

[0020] A polyacrylonitrile fiber composite adsorbent material prepared by the method described above.

[0021] Preferably, the polyacrylonitrile fiber composite adsorbent material has a photothermal response and exhibits a relatively fast tetracycline hydrochloride removal rate under light conditions.

[0022] The present invention also provides the application of the above-mentioned polyacrylonitrile fiber composite adsorbent material in the treatment of antibiotic wastewater.

[0023] Preferably, the antibiotic wastewater treatment specifically includes tetracycline hydrochloride wastewater treatment.

[0024] Preferably, when the polyacrylonitrile fiber composite adsorbent material is applied to the treatment of antibiotic wastewater, especially tetracycline hydrochloride wastewater, under the conditions of light and hydrogen peroxide, the copper-containing sites in the material promote the participation of hydrogen peroxide in the oxidation reaction, causing tetracycline hydrochloride to undergo Fenton-like catalytic transformation, and together with the adsorption and enrichment effect of the composite adsorbent layer, the pollutant removal effect is improved.

[0025] In other embodiments, persulfate can be used as an external oxidant, utilizing copper-containing sites in the material to promote persulfate activation.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention utilizes zinc oxide-assisted in-situ generation of HKUST-1 at room temperature to construct a sodium alginate / carbon black / HKUST-1 composite adsorption layer on the surface of polyacrylonitrile fibers. This improves the material's wettability, mass transfer efficiency, and adsorption site utilization in aqueous phase, while also endowing the material with photothermal responsiveness. Specifically, carbon black, while acting as an adsorbent, also participates in regulating the growth of HKUST-1 and the interfacial mass transfer process, resulting in a faster adsorption and removal rate under light conditions. Specifically, after carbon black is fixed in the sodium alginate gel layer, it provides a rough composite interface and more nucleation and growth sites for the in-situ growth of HKUST-1 on the fiber surface, forming a composite capping layer containing HKUST-1. Furthermore, it endows the composite adsorption material with photothermal responsiveness. Moreover, the enhanced photothermal response of the material due to the introduction of carbon black may be one of the factors influencing the removal process of tetracycline hydrochloride under light conditions.

[0027] 2. The polyacrylonitrile fiber composite adsorbent material prepared by this invention uses PAN fibers as a continuous macroscopic support, giving the adsorbent material a fiber morphology that can be removed and reused as a whole, and thus possessing recyclability; furthermore, by forming Cu²⁺ on the surface of the polyacrylonitrile fibers... + A cross-linked sodium alginate gel layer serves as the carbon black immobilization layer and the HKUST-1 in-situ growth interface; the carbon black is embedded and dispersed in Cu²⁺. + In the cross-linked sodium alginate gel layer, a rough, porous composite interface with photothermal responsiveness is formed. This promotes the in-situ growth of HKUST-1 while giving the material photothermal responsiveness and exhibiting a faster tetracycline hydrochloride removal rate under light irradiation. Simultaneously, the composite adsorption layer formed by sodium alginate, carbon black, and HKUST-1 improves the aqueous wettability of the polyacrylonitrile fibers, thus enhancing the hydrophilicity of the resulting composite adsorption material.

[0028] 3. In the polyacrylonitrile fiber composite adsorbent material prepared by this invention, carbon black, as a photothermal carbon material, together with HKUST-1 constitutes the composite adsorbent layer. The photothermal carbon material can also be selected from one or more of carbon nanotubes and graphene. Carbon black provides a rough interface and photothermal response, while HKUST-1 provides a porous structure, copper nodes, and organic ligand adsorption sites. The addition of carbon black enhances the photothermal response of the composite adsorbent material, and the overall composite material exhibits a faster tetracycline hydrochloride removal rate under illumination.

[0029] Carbon black imparts a stable photothermal response to the material, and the composite adsorbent material exhibits a stable photothermal response and a relatively fast tetracycline hydrochloride removal rate under light conditions, thereby achieving photothermal-assisted rapid adsorption and removal, and possessing excellent cycle stability.

[0030] 4. This invention transforms powdered HKUST-1 into a fiber-supported composite adsorption structure, and utilizes Cu²⁺... + The cross-linked sodium alginate gel layer enables the fixation of photothermal carbon materials and the in-situ growth of HKUST-1, resulting in a stable composite structure of PAN fibers, sodium alginate gel layer, carbon black, and HKUST-1.

[0031] Under conditions of both light and hydrogen peroxide, the light exposure can influence the tetracycline hydrochloride removal process when the composite adsorbent material interacts with hydrogen peroxide. Copper-containing sites in the composite adsorbent material may promote the oxidation reaction of hydrogen peroxide. Adsorption enrichment and Fenton-like catalytic oxidation may jointly affect the removal efficiency of tetracycline hydrochloride in water. Even without the addition of an external oxidant, the composite adsorbent material can still adsorb and remove tetracycline hydrochloride; this process may be related to the HKUST-1 pores, copper nodes, sodium alginate, and carbon black composite interface. Attached Figure Description

[0032] Figure 1 These are scanning electron microscope (SEM) images of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 and the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1. In the figures, (a) is the SEM image of Example 1 and (b) is the SEM image of Comparative Example 1. Figure 2 The figures show the EDS energy spectrum, elemental composition, and elemental surface distribution of the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 of this invention. In the figures, (a) is the elemental superposition diagram of Example 1, (b) is the C elemental surface distribution diagram of Example 1, (c) is the O elemental surface distribution diagram of Example 1, (d) is the Cu elemental surface distribution diagram of Example 1, (e) is the Zn elemental surface distribution diagram of Example 1, (f) is the N elemental surface distribution diagram of Example 1, and (g) is the EDS energy spectrum and elemental composition diagram of Example 1. Figure 3 These are photographs of the water contact angles of the composite adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 of this invention. In the figures, a1 represents the initial state of the water droplet in contact with the composite adsorbent material prepared in Example 1, a2 represents the final wetting state of the water droplet in contact with the composite adsorbent material prepared in Example 1, b1 represents the initial state of the water droplet in contact with the composite adsorbent material prepared in Example 2, b2 represents the final wetting state of the water droplet in contact with the composite adsorbent material prepared in Example 2, c1 represents the initial state of the water droplet in contact with the composite adsorbent material prepared in Example 3, and c2 represents the final wetting state of the water droplet in contact with the composite adsorbent material prepared in Example 4. 3. The final wetting state of the prepared composite adsorbent material upon contact: d1 is the initial state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 1; d2 is the final wetting state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 1; e1 is the initial state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 2; e2 is the final wetting state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 2; f1 is the initial state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 3; f2 is the final wetting state of the water droplet when it comes into contact with the composite adsorbent material prepared in Comparative Example 3. Figure 4 This is a line graph showing the removal rate of tetracycline hydrochloride by the composite adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention under dark conditions. Figure 5 The images show the photothermal heating infrared diagrams of the composite adsorbent materials prepared in Example 1 and Comparative Example 1 during continuous illumination from 0 to 600 s. In the figures, a is the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1, and b is the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1. Figure 6 These are the heating and cooling curves of the composite adsorbent materials prepared in Example 1 and Comparative Example 1 of this invention; Figure 7 This is a comparison diagram of the photothermal cycling stability of the composite adsorbent materials prepared in Example 1 and Comparative Example 1 of this invention; Figure 8 This is a comparison chart of the removal rates of tetracycline hydrochloride by the composite adsorbent material prepared in Example 1 of this invention under dark conditions and under light conditions; Figure 9 These are thermogravimetric curves of the composite adsorbent materials prepared in Example 1, Comparative Examples 1 to 3 of the present invention under a nitrogen atmosphere. Figure 10 This is a nitrogen adsorption-desorption isotherm diagram of the composite adsorbent material prepared in Example 1 of this invention; Figure 11 This is a nitrogen adsorption-desorption pore size distribution diagram of the composite adsorbent material prepared in Example 1 of the present invention; Figure 12This is a bar chart showing the removal effect of the composite adsorbent material prepared in Example 1 of the present invention on tetracycline hydrochloride under different initial pH conditions; Figure 13 This is a graph showing the zeta potential changes of the composite adsorbent material prepared in Example 1 of this invention under different pH conditions; Figure 14 This is a bar chart showing the removal effect of the composite adsorbent material prepared in Example 1 of the present invention on tetracycline hydrochloride under different coexisting cation conditions; Figure 15 This is a graph showing the cycle stability test results of the composite adsorbent material prepared in Example 1 of this invention; Figure 16 These are the XRD patterns of the composite adsorbent material prepared in Example 1 of this invention before and after recycling; Figure 17 These are the infrared spectra of the composite adsorbent material prepared in Example 1 of this invention before and after recycling; Figure 18 This is a line graph showing the removal rate of tetracycline hydrochloride by the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 of this invention under dark and light conditions, with or without the addition of hydrogen peroxide. Figure 19 This is a process flow diagram for preparing polyacrylonitrile fiber composite adsorbent materials according to an embodiment of the present invention. Detailed Implementation

[0033] The present invention will be further illustrated below through specific embodiments. The following embodiments are specific implementations of the present invention, but the implementation of the present invention is not limited to the following embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and are included within the protection scope of the present invention.

[0034] Example 1 This embodiment discloses a method for preparing a polyacrylonitrile fiber composite adsorbent material, including the following steps: Step (1): Disperse 0.3g zinc oxide (ZnO) and 0.5g carbon black (CB) in 50mL of deionized water by ultrasonication for 10min. Then add 1.25g sodium alginate (SA) and stir at room temperature for 12h to obtain SA / CB / ZnO aqueous dispersion. Weigh 1.500g of copper nitrate trihydrate, add it to 50.0mL of deionized water, sonicate until completely dissolved, and then stir magnetically for 15min to obtain a copper nitrate aqueous solution; wherein, based on the volume of deionized water used for preparation, the concentration of copper nitrate trihydrate is 30.0mg / mL. After thoroughly mixing the obtained copper nitrate aqueous solution, 50.0 mL of it was measured for subsequent ionic crosslinking. Weigh 3.360 g of trimellitic acid and dissolve it in 64.0 mL of anhydrous ethanol. Then add 64.0 mL of N,N-dimethylformamide and 64.0 mL of deionized water, and stir until completely dissolved to obtain a trimellitic acid solution. The volume ratio of anhydrous ethanol, N,N-dimethylformamide and deionized water is 1:1:1, and the total volume of the three solvents added is 192.0 mL. Based on the sum of the volumes of the three solvents added, the concentration of trimellitic acid is 17.5 mg / mL. After thoroughly mixing the obtained pyromellitic acid solution, 48.0 mL of it was used for subsequent in-situ growth of HKUST-1. Step (2): After coating the polyacrylonitrile (PAN) fiber with SA / CB / ZnO aqueous dispersion, it is transferred to copper nitrate aqueous solution to complete the ionic cross-linking reaction, and then placed in trimesic acid solution to react and generate HKUST-1 in situ. After washing and drying, SA / CB / HKUST-1 / PAN composite adsorbent material is obtained, namely polyacrylonitrile fiber composite adsorbent material, denoted as SCHP. The specific process includes the following steps: S1. After thoroughly stirring the SA / CB / ZnO aqueous dispersion, immediately measure 50.0 mL; weigh 0.300 g of dried polyacrylonitrile (PAN) fiber, and completely immerse it in the above 50.0 mL SA / CB / ZnO aqueous dispersion. Immerse it three times consecutively at 25°C, with each immersion time being 3 min. After immersion, SA / CB / ZnO / PAN coated fiber is obtained. The impregnation bath ratio was calculated based on the dry weight of PAN fibers and the actual volume of SA / CB / ZnO aqueous dispersion, which was 0.300 g: 50.0 mL, i.e., a material-to-liquid ratio of 1 g: 166.7 mL. After the first and second impregnations, the PAN fibers were completely removed and immediately re-impregnated into the same SA / CB / ZnO aqueous dispersion without drying or other intermediate treatment, so that the SA / CB / ZnO dispersion could fully coat the polyacrylonitrile fibers. After the third impregnation, the resulting SA / CB / ZnO / PAN coated fibers were completely removed. S2 and SA / CB / ZnO / PAN coated fibers were transferred to a copper nitrate aqueous solution and soaked at 25°C for 15 minutes to allow for sufficient ionic crosslinking. After crosslinking was completed, the fibers were removed and washed with deionized water to remove uncrosslinked free copper ions and nitrate ions from the surface, thus obtaining Cu-SA / CB / ZnO / PAN fibers. The bath ratio for the cross-linking reaction is calculated based on the dry mass of the PAN fiber before coating and the actual volume of the copper nitrate aqueous solution, which is 0.300g:50.0mL, i.e., the material-liquid ratio is 1g:166.7mL. S3. Place Cu-SA / CB / ZnO / PAN fibers in a trimesic acid solution and react at 25℃ for 40 min to generate HKUST-1 in situ. After the reaction is complete, remove the fibers and wash them alternately with anhydrous ethanol and deionized water for 3 cycles. In each cycle, wash with anhydrous ethanol once and then with deionized water once. After washing, vacuum dry at 50℃ for 24 h to obtain the SA / CB / HKUST-1 / PAN composite adsorbent material. The in-situ material-to-liquid ratio of HKUST-1 is calculated based on the initial dry mass of PAN fibers and the actual volume of trimesic acid solution, and is 0.300g:48.0mL, or 1g:160.0mL.

[0035] Example 2 This embodiment discloses a method for preparing a polyacrylonitrile fiber composite adsorbent material, including the following steps: Step (1): Disperse 0.200g zinc oxide (ZnO) and 0.400g carbon black (CB) in 50mL of deionized water by ultrasonication for 10min. Then add 1.000g sodium alginate (SA) and stir at room temperature for 12h to obtain SA / CB / ZnO aqueous dispersion. Weigh 1.000g of copper nitrate trihydrate, add it to 50.0mL of deionized water, sonicate until completely dissolved, and then stir magnetically for 15min to obtain a copper nitrate aqueous solution; wherein, based on the volume of deionized water used for preparation, the concentration of copper nitrate trihydrate is 20.0mg / mL. After thoroughly mixing the obtained copper nitrate aqueous solution, 45.0 mL of it was measured for subsequent ionic crosslinking. Weigh 2.880 g of trimellitic acid and dissolve it in anhydrous ethanol. Then add N,N-dimethylformamide and deionized water and stir until completely dissolved to obtain a trimellitic acid solution. The volume ratio of anhydrous ethanol, N,N-dimethylformamide and deionized water is 1:1:1. The total concentration of trimellitic acid is 15.0 mg / mL based on the sum of the volumes of the three solvents.

[0036] After thoroughly mixing the obtained pyromellitic acid solution, 45.0 mL of it was used for subsequent in-situ growth of HKUST-1. Step (2): After coating the polyacrylonitrile (PAN) fiber with SA / CB / ZnO aqueous dispersion, it is transferred to copper nitrate aqueous solution to complete the ionic cross-linking reaction, and then placed in trimesic acid solution to react and generate HKUST-1 in situ. After washing and drying, SA / CB / HKUST-1 / PAN composite adsorbent material is obtained, namely polyacrylonitrile fiber composite adsorbent material, denoted as SCHP-2. The specific process includes the following steps: S1. After thoroughly stirring the SA / CB / ZnO aqueous dispersion, immediately measure 45.0 mL; weigh 0.300 g of dried polyacrylonitrile (PAN) fiber, and completely immerse it in the above 45.0 mL SA / CB / ZnO aqueous dispersion. Immerse it twice consecutively at 25℃, with each immersion time being 2 min. After immersion, SA / CB / ZnO / PAN coated fiber is obtained. The impregnation bath ratio was calculated based on the dry weight of the PAN fibers and the actual volume of the SA / CB / ZnO aqueous dispersion, with a material-to-liquid ratio of 1g:150.0mL. After the first impregnation, the PAN fibers were completely removed and immediately re-immersed in the same SA / CB / ZnO aqueous dispersion without drying or other intermediate treatment, so that the SA / CB / ZnO dispersion could fully coat the polyacrylonitrile fibers. After the second impregnation, the resulting SA / CB / ZnO / PAN coated fibers were completely removed. S2 and SA / CB / ZnO / PAN coated fibers were transferred to a copper nitrate aqueous solution and soaked at 25°C for 10 min to allow for sufficient ionic crosslinking. After crosslinking was completed, the fibers were removed and washed with deionized water to remove uncrosslinked free copper ions and nitrate ions from the surface, thus obtaining Cu-SA / CB / ZnO / PAN fibers. The bath ratio for the cross-linking reaction is calculated based on the dry mass of the PAN fiber before coating and the actual volume of the copper nitrate aqueous solution, with a material-to-liquid ratio of 1g:150.0mL. S3. Place Cu-SA / CB / ZnO / PAN fibers in a trimesic acid solution and react at 25°C for 30 min to generate HKUST-1 in situ. After the reaction is complete, remove the fibers and wash them alternately with anhydrous ethanol and deionized water for 3 cycles. In each cycle, wash with anhydrous ethanol once and then with deionized water once. After washing, vacuum dry at 50°C for 24 h to obtain the SA / CB / HKUST-1 / PAN composite adsorbent material. The material-to-liquid ratio of HKUST-1 generated in situ is calculated based on the initial dry mass of PAN fibers and the actual volume of trimesic acid solution, with a material-to-liquid ratio of 1g:150.0mL.

[0037] Example 3 This embodiment discloses a method for preparing a polyacrylonitrile fiber composite adsorbent material, including the following steps: Step (1): Disperse 0.480g zinc oxide (ZnO) and 0.720g carbon black (CB) in 60mL of deionized water by ultrasonication for 10min. Then add 1.800g sodium alginate (SA) and stir at room temperature for 12h to obtain SA / CB / ZnO aqueous dispersion. Weigh 2.400g of copper nitrate trihydrate, add it to 60.0mL of deionized water, sonicate until completely dissolved, and then stir magnetically for 15min to obtain a copper nitrate aqueous solution; wherein, based on the volume of deionized water used for preparation, the concentration of copper nitrate trihydrate is 40.0mg / mL. After thoroughly mixing the obtained copper nitrate aqueous solution, 60.0 mL of it was measured for subsequent ionic crosslinking. Weigh 3.840 g of trimellitic acid and dissolve it in anhydrous ethanol. Then add N,N-dimethylformamide and deionized water and stir until completely dissolved to obtain a trimellitic acid solution. The volume ratio of anhydrous ethanol, N,N-dimethylformamide and deionized water is 1:1:1. The total concentration of trimellitic acid is 20.0 mg / mL based on the sum of the volumes of the three solvents.

[0038] After thoroughly mixing the obtained pyromellitic acid solution, 60.0 mL of it was used for subsequent in-situ growth of HKUST-1. Step (2): After coating the polyacrylonitrile (PAN) fiber with SA / CB / ZnO aqueous dispersion, it is transferred to copper nitrate aqueous solution to complete the ionic crosslinking reaction, and then placed in trimesic acid solution to react so that HKUST-1 is generated in situ. After washing and drying, SA / CB / HKUST-1 / PAN composite adsorbent material is obtained, namely polyacrylonitrile fiber composite adsorbent material, denoted as SCHP-3. The specific process includes the following steps: S1. After thoroughly stirring the SA / CB / ZnO aqueous dispersion, immediately measure 60.0 mL; weigh 0.300 g of dried polyacrylonitrile (PAN) fiber, and completely immerse it in the above 60.0 mL SA / CB / ZnO aqueous dispersion. Immerse it continuously 4 times at 25℃, with each immersion time being 5 min. After the immersion is completed, SA / CB / ZnO / PAN coated fiber is obtained. The impregnation bath ratio was calculated based on the dry weight of PAN fibers and the actual volume of SA / CB / ZnO aqueous dispersion, with a material-to-liquid ratio of 1g:200.0mL. After the first, second, and third impregnations, the PAN fibers were completely removed and immediately re-impregnated into the same SA / CB / ZnO aqueous dispersion without drying or other intermediate treatment, so that the SA / CB / ZnO dispersion fully coated the polyacrylonitrile fibers. After the fourth impregnation, the resulting SA / CB / ZnO / PAN coated fibers were completely removed. S2 and SA / CB / ZnO / PAN coated fibers were transferred to a copper nitrate aqueous solution and soaked at 25°C for 20 minutes to allow for sufficient ionic crosslinking. After crosslinking was completed, the fibers were removed and washed with deionized water to remove uncrosslinked free copper ions and nitrate ions from the surface, thus obtaining Cu-SA / CB / ZnO / PAN fibers. The bath ratio for the cross-linking reaction is calculated based on the dry mass of the PAN fiber before coating and the actual volume of the copper nitrate aqueous solution, with a material-to-liquid ratio of 1g:200.0mL. S3. Place Cu-SA / CB / ZnO / PAN fibers in a pyromellitic acid solution and react at 25°C for 50 min to generate HKUST-1 in situ. After the reaction is complete, remove the fibers and wash them alternately with anhydrous ethanol and deionized water for 3 cycles. In each cycle, wash with anhydrous ethanol once and then with deionized water once. After washing, vacuum dry at 50°C for 24 h to obtain the SA / CB / HKUST-1 / PAN composite adsorbent material. The material-to-liquid ratio of HKUST-1 generated in situ is calculated based on the initial dry mass of PAN fibers and the actual volume of trimesic acid solution, with a material-to-liquid ratio of 1g:200.0mL.

[0039] Comparative Example 1 The difference from Example 1 is that the amount of carbon black added in step (1) is adjusted to 0g, that is, no carbon black is added; the amount of other raw materials, operating steps and process conditions are the same as in Example 1, and the SA / HKUST-1 / PAN composite adsorbent material is obtained, which is denoted as SHP.

[0040] Comparative Example 2 The difference from Example 1 is that the amount of zinc oxide added in step (1) is adjusted to 0g, that is, no zinc oxide is added; after the copper nitrate ion crosslinking is completed and the material is washed with deionized water, the HKUST-1 in-situ growth step in the trimesic acid solution is no longer performed, and subsequent washing and vacuum drying are carried out directly. The amount of other raw materials and process conditions are the same as in Example 1, and the SA / CB / PAN composite adsorbent material is obtained, denoted as SCP.

[0041] Comparative Example 3 The difference from Example 1 is that the amount of zinc oxide and carbon black added in step (1) is adjusted to 0g, that is, no zinc oxide and carbon black are added; after the copper nitrate ion crosslinking is completed and the material is washed with deionized water, the HKUST-1 in-situ growth step in the trimesic acid solution is no longer performed, and subsequent washing and vacuum drying are carried out directly. The amount of other raw materials and process conditions are the same as in Example 1, and the SA / PAN composite adsorbent material is obtained, denoted as SP.

[0042] In the above examples and comparative examples, the PAN fibers used were commercially available continuous fiber aggregates with a linear density of 70 tex; zinc oxide was purchased from Shanghai Maclean Biochemical Co., Ltd., with a particle size of ≤100 nm and product number Z141332-100g; carbon black was ordinary carbon black, purchased from Shanghai Maclean Biochemical Co., Ltd., with a particle size of 100 nm and product number C914875-100g; sodium alginate was low-viscosity sodium alginate, purchased from J&K Scientific Ltd., with a viscosity of 20-100 Cp and product number 603390.

[0043] In other embodiments, the carbon black in step (1) can be replaced with carbon materials such as carbon nanotubes and graphene that have the ability to absorb light and convert light and heat.

[0044] Experimental data characterization and performance testing Figure 1 These are scanning electron microscope (SEM) images of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 and the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1; wherein, Figure 1 (a) is a scanning electron microscope image of Example 1. Figure 1 Image (b) is a scanning electron microscope image of Comparative Example 1. (From...) Figure 1 It can be seen that there are significant differences in the surface morphology of the two groups of materials. In Comparative Example 1, no carbon black was added, and more polyhedral particles with clear boundaries can be observed on its surface, while relatively flat areas can still be observed between some particles.

[0045] In Example 1, after adding carbon black, the material surface mainly exhibited a rough, continuous granular coating, and the boundaries of the independent polyhedral particles were not as clear as in Comparative Example 1. These results indicate that the addition of carbon black altered the morphology and particle coating state of the composite layer on the fiber surface, resulting in a more continuous, rough composite coating layer on the material surface. Therefore... Figure 1 The results reflect the differences in surface morphology and particle coverage between the materials of Example 1 and Comparative Example 1.

[0046] The specific principle is as follows: In an SA / CB / ZnO aqueous dispersion, carbon black particles are dispersed in a continuous sodium alginate phase and surrounded by sodium alginate molecular chains. When the SA / CB / ZnO / PAN coated fibers are immersed in a copper nitrate aqueous solution, Cu²⁺… +Carbon black diffuses into the coating layer and coordinates with carboxylate groups on adjacent sodium alginate molecular chains, forming an insoluble three-dimensional ionic cross-linked network. With the formation of this network, pre-dispersed carbon black particles are embedded and confined within the gel layer. Simultaneously, van der Waals interactions between the sodium alginate molecular chains and the carbon black surface, as well as the potential hydrogen bonds between oxygen-containing groups on the carbon black surface and the hydroxyl or carboxyl groups of sodium alginate, further enhance the stability of carbon black in the gel layer. Therefore, the fixation of carbon black in the gel layer mainly originates from the physical embedding, spatial confinement, and interfacial adsorption of the ionic cross-linked network.

[0047] The effect of carbon black on the in-situ growth of HKUST-1 is not only to increase the surface roughness of the material. Carbon black possesses a large interfacial area, sp² conjugated carbon structure, as well as surface defects and a small number of oxygen-containing sites. Among these, the defects and oxygen-containing sites on the carbon black surface may affect Cu²... + Adsorption occurs, and its conjugated carbon structure facilitates the adsorption of pyromellitic acid containing aromatic rings via π-π interactions and van der Waals interactions. These interactions favor Cu²⁺. + Trimethylbenzene acid is enriched near the composite interface formed by carbon black and Cu-SA gel, and carbon black is immobilized on Cu²⁺. + Cross-linking the sodium alginate gel layer can alter the surface roughness and local interfacial environment of the composite layer, and may affect the interfacial growth state of HKUST-1. The microscopic composite interface formed by carbon black particles can also restrict the crystal growth space to a certain extent, thereby facilitating the formation of a more continuous and uniformly distributed HKUST-1 loading layer.

[0048] Figure 2 This is the EDS energy spectrum, elemental composition, and elemental surface distribution diagram of the SA / CB / HKUST-1 / PAN composite adsorbent (SCHP) prepared in Example 1. Figure 2It was found that C, N, O, Cu, and Zn elements were detected within the selected EDS test area. The elemental surface distribution results showed that the signals of C, O, Cu, Zn, and N elements were mainly distributed along the material's location, indicating the presence of copper and zinc components within the tested material area. The semi-quantitative EDS results showed that the mass percentages of C, N, O, Cu, and Zn elements were 65.68%, 1.75%, 26.79%, 5.10%, and 0.69%, respectively. Among these, N element was mainly related to the PAN matrix, and the detection of Cu element indicated the presence of copper components within the tested material area. The mass percentage of Zn element within the selected test area was 0.69%, indicating the detection of a small amount of Zn element within this area. This is because zinc oxide can assist in the formation of HKUST-1 at room temperature. During the preparation process, zinc oxide first reacts with copper nitrate to form a hydroxy double salt intermediate containing Zn and Cu. After the addition of trimellitic acid, this intermediate further participates in the formation of HKUST-1. Some zinc-containing species enter the liquid phase and are removed during subsequent washing, which is consistent with the result that only a small amount of Zn was detected in the selected area. Since EDS is a local semi-quantitative analysis, it cannot be used alone to determine the specific chemical form of Zn in the final material, the overall content of the material, or whether zinc oxide is completely retained. Combining the above preparation principle and process, the reason why only a small amount of Zn was detected in the selected EDS test area is that some zinc-containing species enter the liquid phase during the formation of HKUST-1 in the intermediate and are removed during subsequent washing with ethanol and deionized water. The role of zinc oxide mainly occurs during the preparation process and is not as a major component of the final material.

[0049] Figure 3 These are photographs of the water contact angles of the composite adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3. Figure 3 In the diagram, a1 to f1 represent the initial state when the water droplet comes into contact with the material, and a2 to f2 represent the corresponding final wetting state.

[0050] Depend on Figure 3 As shown in a1 to c1 and a2 to c2, the polyacrylonitrile fiber composite adsorbent material (SCHP) prepared in Example 1 was completely wetted at 4.40 s; the composite adsorbent materials prepared in Examples 2 and 3 were completely wetted at 5.52 s and 5.14 s, respectively. It is evident that all three examples achieved complete wetting within 5.52 s, with Example 1 having the shortest wetting time, followed by Example 3, and Example 2 slightly longer. These results indicate that the composite adsorbent materials prepared using the lower, middle, and upper limits of the raw material dosage and process parameter ranges defined in this invention all exhibit relatively fast aqueous phase wetting speeds, with the middle parameter combination used in Example 1 showing even faster wetting behavior under the test conditions.

[0051] Depend on Figure 3As shown in d1 to f1 and d2 to f2, the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1 was completely wetted at 7.11 s, while the SA / CB / PAN composite adsorbent material prepared in Comparative Example 2 was completely wetted at 9.31 s. The SA / PAN composite adsorbent material prepared in Comparative Example 3 maintained a water contact angle of approximately 30° at the test endpoint, and did not show complete wetting. In Comparative Example 1, the other preparation conditions were the same as those in Comparative Example 1. The main difference was that Comparative Example 1 did not contain carbon black. After adding carbon black, the complete wetting time was shortened from 7.11 s to 4.40 s, indicating that the introduction of carbon black into the composite adsorbent layer helps to accelerate water droplet spreading. Comparative Examples 2 and 3 did not involve in-situ growth of HKUST-1. The main difference was that Comparative Example 2 contained carbon black. Comparative Example 2 was able to be completely wetted at 9.31 s, while Comparative Example 3 still retained a water contact angle of approximately 30° at the test endpoint, further demonstrating that the surface structure constructed with carbon black helps to improve the dynamic wetting performance of the material.

[0052] Figure 4 This is a line graph showing the removal rate of tetracycline hydrochloride by the composite adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 under dark conditions.

[0053] The adsorption and removal experiment of antibiotics in water under dark conditions included the following steps: First, 0.1 g of the composite adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 were added to 20 mL of tetracycline hydrochloride aqueous solution, respectively. The initial concentration of tetracycline hydrochloride was 50 mg / L. The initial pH of the tetracycline hydrochloride aqueous solution was measured to be approximately 5.8 before the addition of the composite adsorbent materials, and no pH adjustment was performed during the experiment. The reaction was started under static, light-protected conditions. During the reaction, the absorbance of the solution was measured at the maximum absorption wavelength of tetracycline hydrochloride λ = 357 nm at regular intervals, and the removal rate of tetracycline hydrochloride was calculated accordingly.

[0054] from Figure 4As can be seen, under dark conditions, the removal rates of tetracycline hydrochloride by the composite adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 gradually increased with the extension of adsorption time. Among them, the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 had the highest removal rate at 360 min, reaching 83.47%; the composite adsorbents prepared in Examples 2 and 3 had removal rates of 79.82% and 82.34% at 360 min, respectively, both higher than the three comparative examples. The SA / HKUST-1 / PAN composite adsorbent prepared in Comparative Example 1 had a removal rate of 74.87% at 360 min; the SA / CB / PAN composite adsorbents prepared in Comparative Example 2 and Comparative Example 3 had removal rates of 63.39% and 55.36%, respectively. The removal rates of the three examples ranged from 79.82% to 83.47%, with Example 1 being 3.65 percentage points and 1.13 percentage points higher than Examples 2 and 3, respectively, and Example 3 being 2.52 percentage points higher than Example 2. It can be seen that, within the range of raw material dosage and process parameters defined by the present invention, the composite adsorbent materials prepared using the lower limit, intermediate value and upper limit value all have good adsorption and removal capacity of tetracycline hydrochloride. Among them, Example 1, which uses the intermediate parameter combination, performs the best, while Example 3, which uses the upper limit parameter combination, is similar to Example 1.

[0055] The above results indicate that composite materials formed with different raw material compositions and preparation steps exhibit different tetracycline hydrochloride removal performances. The main difference between Example 1 and Comparative Example 1 is the addition of carbon black, and the main difference between Comparative Example 2 and Comparative Example 3 is also the addition of carbon black. In both comparisons, the materials with added carbon black showed higher tetracycline hydrochloride removal rates, indicating that under the corresponding preparation conditions, the addition of carbon black is beneficial to improving the tetracycline hydrochloride removal performance of the materials. Figure 1 Scanning electron microscopy results show that the addition of carbon black formed a relatively rough and continuous composite coating layer on the material surface, indicating that the addition of carbon black altered the morphology and particle coverage of the material surface. Combined with... Figure 3The water contact angle test results show that the complete wetting time of Example 1 is shorter than that of Comparative Example 1, indicating that the addition of carbon black is beneficial to improving the dynamic wetting performance of the material. The changes in the surface morphology and wetting behavior mentioned above may affect the contact process between the tetracycline hydrochloride solution and the composite adsorption layer. The removal rate of Example 1 is slightly higher than that of Examples 2 and 3, indicating that within the scope defined by this invention, different combinations of raw material dosage and process parameters can all achieve good tetracycline hydrochloride removal effects. Examples 2, 1, and 3 use the lower limit, middle value, and upper limit of the range, respectively, and their performance differences may be affected by factors such as the thickness of the composite layer, the degree of crosslinking, the HKUST-1 loading state, and the interfacial mass transfer resistance. The existing results are used to illustrate that the above three parameter combinations can all be implemented. Examples 2 and 3 still achieved removal rates of 79.82% and 82.34% respectively after 360 min, indicating that good adsorption performance can be obtained at both ends of the range.

[0056] Figures 5 to 7 In the photothermal test, 0.1g of dried fibrous sample was weighed and laid flat. The light source was a PL-XQ500W simulated daylight xenon lamp with a built-in 500W high-pressure short-arc spherical xenon lamp, with a emission spectrum range of 300-2500nm. The light source outlet was about 23cm away from the sample, and the irradiance on the sample surface was 1kW / m². Figure 5 Record infrared thermal images during continuous illumination from 0 to 600 seconds; Figure 6 The light source was turned on at 0s and continued to irradiate for about 650s before being turned off. The natural cooling process was then recorded. Figure 7 Each cycle involves illuminating the lamp for 600 seconds, followed by turning it off and allowing it to cool naturally for 600 seconds, for a total of 15 cycles. Figure 5 Figure a is an infrared image of the photothermal temperature rise of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 during continuous illumination from 0 to 600 s. All time points listed in the figure represent the heating phase after the light is turned on; the cooling process after the light is turned off is not shown. Figure 5 As can be seen from Figure a, the overall temperature of the sample was close to room temperature before the light was turned on; 15 seconds after the light was turned on, the central region of the sample showed a significant temperature rise, and the high-temperature region further intensified between 30 and 60 seconds. As the illumination time was extended to 120, 240, 360, and 600 seconds, the center of the sample still maintained a significant hot zone, indicating that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 can continuously generate a photothermal response under illumination.

[0057] This result indicates that carbon black is fixed in Cu²⁺. +Even after cross-linking with sodium alginate gel, it still maintains strong light absorption and photothermal conversion capabilities, and forms a stable local thermal field in the composite adsorbent material. The temperature rise in Example 1 is higher than that in Comparative Example 1, indicating that the addition of carbon black significantly enhances the photothermal response of the material.

[0058] Figure 5 Figure b shows the photothermal temperature rise of the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1 during continuous illumination from 0 to 600 s. The time points listed in the figure also belong to the temperature rise stage after the light is turned on. Figure 5 As can be seen from b, Comparative Example 1 also showed a certain temperature rise in the central region after illumination, but its heat range and temperature level were lower than those of Example 1. Figure 5 a and Figure 5 b uses the same fixed color standard range of 25–75℃. The quantitative comparison of the actual highest temperatures of the two samples is based on... Figure 6 The temperature data shown is accurate. Figure 5 a and Figure 5 The values ​​for b all use a fixed color scale range of 25–75°C to show the surface temperature distribution of the two samples during continuous illumination. The upper limit of 75°C only indicates the display range of the infrared image and does not represent the highest measured temperature of the sample. Figure 6 These are temperature change curves of the sample center recorded under the same sample and illumination conditions. The highest temperatures of Example 1 and Comparative Example 1 are approximately 64℃ and 41℃, respectively. Therefore, a quantitative comparison of the photothermal heating capabilities of the two samples is based on... Figure 6 The temperature data shown are accurate. Since the main difference between Example 1 and Comparative Example 1 is the presence or absence of carbon black, the above results indicate that the addition of carbon black enhances the photothermal response of the composite adsorbent material.

[0059] The comparative results show that, under the same test conditions, Example 1 with added carbon black exhibits a more significant photothermal response than Comparative Example 1 without carbon black. The carbon black enables the SA / CB / HKUST-1 / PAN composite adsorbent material to form a stronger local thermal field under illumination, providing conditions for subsequent photothermal-assisted adsorption and removal of tetracycline hydrochloride. While the SA / HKUST-1 / PAN composite adsorbent material without carbon black possesses HKUST-1 adsorption sites, its photothermal response intensity is lower than that of Example 1 containing carbon black due to the lack of significant photothermal enhancement.

[0060] Figure 6 The figures show the temperature rise and fall curves of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 and the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1. During the test, the light source was turned on at 0s, irradiated continuously for approximately 650s, and then turned off. The natural cooling process of the samples was then recorded. Figure 6As can be seen, the temperatures of Example 1 and Comparative Example 1 gradually increased during illumination, reaching maximum temperatures of approximately 64°C and 41°C, respectively. After the light was turned off, the temperatures of both samples gradually decreased, indicating that their temperature changes corresponded to the on and off states of external light. Figure 6 The comparison between Example 1 and Comparative Example 1 shows that the significant difference in temperature rise indicates that carbon black is the main reason for the strong photothermal response obtained in Example 1. Compared with the SA / HKUST-1 / PAN composite adsorbent without carbon black, the SA / CB / HKUST-1 / PAN composite adsorbent with carbon black can form a higher local temperature under the same light conditions, indicating that carbon black can still effectively absorb light energy and convert it into heat energy after being fixed in the sodium alginate gel layer. This result further proves that carbon black endows the composite adsorbent with a significant photothermal response, forming a local thermal field on the fiber surface and in the nearby aqueous phase. Therefore, the addition of carbon black enhances the photothermal response performance of Example 1.

[0061] Figure 7 This is a comparison of the photothermal cycling stability of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 and the SA / HKUST-1 / PAN composite adsorbent material prepared in Comparative Example 1. Each cycle included 600 s of lamp-on irradiation and 600 s of natural cooling after lamp-off, for a total of 15 cycles, and the highest temperature of each cycle was recorded. Figure 7 As can be seen, during 15 consecutive light exposure cycles, the highest temperature of Example 1 remained at approximately 63°C to 64°C, with minimal fluctuations between cycles; the highest temperature of Comparative Example 1 remained at approximately 39°C. Neither material showed significant temperature decay, but the stable temperature of Example 1 was significantly higher than that of Comparative Example 1.

[0062] Based on the compositional differences between the composite adsorbents prepared in Example 1 and Comparative Example 1, it can be seen that the higher and more stable cycling heating capacity of Example 1 mainly originates from the introduction of carbon black. The carbon black is coated with Cu²⁺. + After the cross-linked sodium alginate gel layer was fixed, it still maintained its light absorption and photothermal conversion capabilities during multiple light irradiation cycles, indicating that the photothermal function of carbon black did not show significant attenuation during multiple light irradiation cycles, and the composite adsorption layer has good photothermal cycling stability.

[0063] This result is directly significant for understanding the stability of the SA / CB / HKUST-1 / PAN composite adsorbent material in this invention after multiple light-irradiation cycles. Example 1 not only exhibits a significant localized thermal effect during a single light irradiation but also maintains a stable photothermal response after multiple cycles. This indicates that the composite structure formed between the carbon black, sodium alginate gel layer, and PAN fibers can support repeated use of the material, providing stable thermal response conditions for subsequent photothermal-assisted adsorption and removal of tetracycline hydrochloride.

[0064] Figure 8 This is a comparison chart of the removal rates of tetracycline hydrochloride by the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 under dark and light conditions.

[0065] The adsorption and removal experiment of antibiotics in water under light conditions included the following steps: First, 0.1 g of the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 was added to 20 mL of tetracycline hydrochloride aqueous solution. The initial concentration of tetracycline hydrochloride was 50 mg / L. The initial pH of the tetracycline hydrochloride aqueous solution used was measured to be 5.8 before the addition of the composite adsorbent material. No pH adjustment was performed during the experiment, and the reaction began under static illumination. The illumination was provided by a PL-XQ500W simulated daylight xenon lamp, with a built-in 500W high-pressure short-arc spherical xenon lamp and a emission spectrum range of 300–2500 nm. The light source outlet was approximately 23 cm above the stage surface. By adjusting the operating current of the light source and the placement height of the reaction system, the irradiance at the surface of the reaction solution reached one solar intensity, i.e., 1 kW / m². During the reaction, the absorbance of the solution was measured at regular intervals at the maximum absorption wavelength of tetracycline hydrochloride, λ = 357 nm, and the removal rate of tetracycline hydrochloride was calculated accordingly. Figure 8 The light source, emission spectrum range, light source distance, and irradiance intensity used are similar to those of the light source used. Figures 5 to 7 The photothermal tests are the same. The difference is that... Figures 5 to 7 The photothermal response was tested using a 0.1g dry fibrous sample. Figure 8 Then, 0.1g of the composite adsorbent was added to 20mL of tetracycline hydrochloride aqueous solution for static light adsorption experiment.

[0066] from Figure 8 As can be seen, the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 exhibits a significantly faster removal rate of tetracycline hydrochloride under light conditions than under dark conditions. During dark adsorption, the removal rate of tetracycline hydrochloride by the composite adsorbent gradually increases over time, reaching approximately 53% at 60 min and approximately 83% at 360 min. Under light conditions, the removal rate approaches 90% at 60 min, then slowly increases, reaching approximately 95% at 360 min. This indicates that light irradiation not only leads to a slight increase in the final removal rate but also significantly enhances the initial adsorption and removal rate of the composite adsorbent.

[0067] Combination Figures 5 to 7 The photothermal response test results show that the addition of carbon black enhanced the photothermal response of Example 1; Figure 8This indicates that the tetracycline hydrochloride removal rate of the composite material in Example 1 under illumination is higher than that under dark conditions. The above results illustrate the influence of carbon black on the photothermal response of the material and the influence of illumination on the overall removal result, demonstrating that the composite material in Example 1 has an effect of light-assisted removal of tetracycline hydrochloride.

[0068] Figure 9 These are thermogravimetric curves of the composite adsorbent materials prepared in Example 1, Comparative Examples 1 to 3, under a nitrogen atmosphere. Figure 9 It can be seen that all four composite adsorbents gradually lose weight with increasing temperature, and the overall trends of their thermogravimetric curves are quite similar, indicating that they have similar thermal decomposition processes. Below 240℃, the remaining mass of all four materials remains above approximately 80%, indicating that significant thermal decomposition has not yet occurred.

[0069] The SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 maintained a residual mass of over 90% within the temperature range of approximately 50–180°C, indicating that the composite material has good initial mass retention capability. The SA / HKUST-1 / PAN composite adsorbent prepared in Comparative Example 1 had a relatively low residual mass within the temperature range of approximately 500–800°C, which may be related to the continuous decomposition and charring degree of organic components such as the HKUST-1 organic ligand and the alginate composite layer. The SA / CB / PAN composite adsorbents prepared in Comparative Example 2 and Comparative Example 3 maintained relatively high residual masses within the temperature range of approximately 400–800°C, suggesting that the charring behavior of carbon black and the cross-linked alginate and PAN matrix may contribute to the high-temperature residual mass.

[0070] The actual temperatures involved in conventional water treatment, adsorption cycles, and the photothermal assisted adsorption of this application are all far lower than the aforementioned significant thermal decomposition temperatures. Therefore, from a thermal stability perspective, Example 1, after simultaneously introducing carbon black and HKUST-1, can still maintain good mass stability within the actual operating temperature range and is not prone to significant thermal weight loss due to photothermal heating or conventional adsorption treatment. This material, while achieving the photothermal response of carbon black and the adsorption function of HKUST-1, can meet the temperature stability requirements of the photothermal assisted adsorption process, providing a thermal stability basis for its photothermal response and photothermal assisted adsorption removal.

[0071] Figure 10 This is the nitrogen adsorption-desorption isotherm diagram of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1. From... Figure 10As can be seen, the material exhibits a type IV isotherm accompanied by an H3-type hysteresis loop, indicating that its pore structure is predominantly mesoporous / macroporous. This pore structure mainly originates from the packing gaps between the PAN fiber skeleton, the sodium alginate polymer gel layer, carbon black particles, and HKUST-1 crystals, rather than a single microporous structure. This open pore structure facilitates the spread and penetration of the aqueous phase into the composite adsorption layer on the fiber surface, making it easier for tetracycline hydrochloride molecules to access the outer surface of HKUST-1 crystals, pore entrances, copper nodes, and organic ligand sites, thereby improving the accessibility of adsorption sites. Combined with the aforementioned rough interface and photothermal response caused by carbon black, this mesoporous / macroporous structure can provide a channel basis for the diffusion of pollutants in the aqueous phase and interfacial mass transfer.

[0072] Figure 11 This is a nitrogen adsorption-desorption pore size distribution diagram of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1. From... Figure 11 As can be seen, the average pore size of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 is 3.84 nm, which falls within the mesoporous range and can provide channels for the diffusion of tetracycline hydrochloride molecules. Combined with the rapid wetting characteristics of this material, it indicates that the SA / CB / HKUST-1 / PAN composite adsorbent material not only possesses an accessible pore structure but also promotes sufficient contact between the tetracycline hydrochloride-containing solution and the composite adsorbent layer on the fiber surface. This allows tetracycline hydrochloride molecules to more easily reach the outer surface of the HKUST-1 crystal, pore entrances, copper nodes, and organic ligand sites, thereby improving the utilization efficiency of the adsorption sites. Therefore, this mesoporous structure also provides structural support for the photothermal-assisted rapid adsorption and removal in Example 1.

[0073] The tetracycline hydrochloride removal experiment under different initial pH conditions included the following steps: 20 mL of tetracycline hydrochloride aqueous solution with an initial concentration of 50 mg / L was taken. Before adding the composite adsorbent material, the initial pH of each group of solutions was adjusted dropwise using 0.1 mol / L hydrochloric acid aqueous solution or 0.1 mol / L sodium hydroxide aqueous solution, and measured using a pH meter to achieve initial pH values ​​of 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11, respectively. Subsequently, 0.1 g of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 was added, and the reaction was carried out under static light-protected conditions for 360 min. After the reaction, the absorbance of the solution was measured at the maximum absorption wavelength of tetracycline hydrochloride λ = 357 nm, and the tetracycline hydrochloride removal rate was calculated. Except for the different initial pH values, all other experimental conditions were kept consistent for each group. Figure 12 The bar chart shows the removal effect of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 on tetracycline hydrochloride under different initial pH conditions. Figure 12 The columns in the middle, from left to right, correspond to the experimental groups with initial pH values ​​of 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11, respectively. Figure 12 It can be seen that when the initial pH of the tetracycline hydrochloride solution increases from 2 to 11, the removal rate of tetracycline hydrochloride by the composite adsorbent material generally shows a trend of first increasing and then decreasing. Within the initial pH range of 3–8, the removal rate remains at a high level, indicating that the material has good applicability under weakly acidic to near-neutral conditions. The removal effect is particularly good at initial pH values ​​of 6 and 8, demonstrating that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 can maintain a high adsorption and removal capacity within the pH range of common antibiotic wastewater.

[0074] Figure 12 The results also indicate that the removal of tetracycline hydrochloride by the SA / CB / HKUST-1 / PAN composite adsorbent material does not solely rely on a single electrostatic adsorption process. Under different initial pH conditions, the surface charge of the composite adsorbent material and the existing form of tetracycline hydrochloride both change. The composite adsorbent material still maintains good removal efficiency over a relatively wide pH range. This suggests that pore adsorption, hydrogen bonding, oxygen-containing functional group interactions, and coordination involving copper nodes in HKUST-1 all participate in the adsorption process, synergistically improving the removal efficiency of the composite adsorbent material for tetracycline hydrochloride.

[0075] Figure 13 This is a graph showing the zeta potential changes of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 under different pH conditions. Figure 13 It can be seen that as the pH value of the solution increases, the surface potential of the composite adsorption material gradually changes from positive to negative, and its isoelectric point is approximately 5.83. When the pH value is below 5.83, the material surface is positively charged; when the pH value is above 5.83, the material surface is negatively charged.

[0076] Combination Figure 12 The results of tetracycline hydrochloride removal under different initial pH conditions show that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 maintains a high removal rate for tetracycline hydrochloride within a pH range of 3-8. Especially after the pH value exceeds the isoelectric point, the material surface becomes negatively charged, yet it still maintains a good removal effect. This indicates that the adsorption of tetracycline hydrochloride by this composite adsorbent material depends not only on electrostatic attraction but also on the pore structure of HKUST-1, the coordination of copper nodes, the interaction of oxygen-containing functional groups on the surfaces of sodium alginate and carbon black, and hydrogen bonding.

[0077] Therefore, it can be seen that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 has a certain removal capacity in a wide initial pH range, and can stably exert its adsorption effect under weakly acidic to near-neutral conditions, making it suitable for application in actual antibiotic wastewater treatment scenarios with large pH fluctuations.

[0078] In the tetracycline hydrochloride removal experiments under different coexisting cation conditions, a blank group without coexisting salts and experimental groups with NaCl, KCl, and CaCl2 were set up respectively. Each group used 20 mL of 50 mg / L tetracycline hydrochloride aqueous solution, and added NaCl, KCl, or CaCl2 respectively to make the final concentration of the corresponding salt 0.01 mol / L. The pH of the solution was not artificially adjusted. Then, 0.1 g of the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 was added, and the reaction was carried out under static light-protected conditions for 360 min. After the reaction, the tetracycline hydrochloride removal rate was measured. Figure 14 The removal efficiency of the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 for tetracycline hydrochloride under different coexisting cation conditions is shown. Figure 14 It can be seen that in the blank system without the addition of coexisting ions, the composite adsorbent material has the highest removal rate of tetracycline hydrochloride; with the addition of Na... + K + and Ca² + Subsequently, the removal rates of tetracycline hydrochloride by the composite adsorbent materials decreased to varying degrees, but the composite adsorbent materials still maintained a certain adsorption capacity. Among them, Na... + and K + It has little impact on the removal effect, Ca² + The inhibitory effect is relatively obvious.

[0079] The above results demonstrate that the SA / CB / HKUST-1 / PAN composite adsorbent prepared in Example 1 still exhibits good anti-interference ability in the presence of common monovalent cations. In Na + K + and Ca² + Under separate conditions, the material in Example 1 still maintains its tetracycline hydrochloride removal capacity, indicating that the adsorption process of this composite adsorbent material is jointly contributed by adsorption at HKUST-1 pores and surface sites, hydrogen bonding, oxygen-containing functional group interactions, and coordination interactions involving copper nodes in HKUST-1. + The inhibition of removal efficiency is more pronounced, possibly due to its strong charge shielding effect and competition for some adsorption sites. This characteristic helps the material maintain a relatively stable treatment effect in actual antibiotic wastewater when faced with interference from common inorganic cations.

[0080] In the cyclical adsorption experiment, 0.1 g of the composite adsorbent prepared in Example 1 was added to 20 mL of a 50 mg / L tetracycline hydrochloride aqueous solution each time. The initial pH of the solution was approximately 5.8, and no artificial adjustment was made. Adsorption lasted for 360 min. After adsorption, the composite adsorbent was immersed in 50 mL of anhydrous ethanol and desorbed by shaking at room temperature for 3 h. Subsequently, it was thoroughly washed with deionized water and vacuum dried at 50 °C for 24 h. The completion of the above adsorption, desorption, washing, and drying process was counted as one cycle, and a total of 4 cycles were performed. Figure 15 The graph shows the cycle stability test results of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1. Figure 15 It can be seen that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 has a high removal rate of tetracycline hydrochloride during the first use. After four adsorption-regeneration cycles, the removal rate still remains above 77%, indicating that the composite adsorbent material still has good adsorption capacity after repeated use. The removal rate decreased slightly during the cycle, which may be related to the fact that some adsorption sites were occupied by pollutant residues, the regeneration process did not completely restore all sites, and a small amount of surface component loss. However, the overall decrease was small, indicating that the SA / CB / HKUST-1 / PAN composite adsorbent material has good reusability.

[0081] Figure 16 and Figure 17 In this context, "before recycling" refers to a fresh sample that has not been used for adsorption, while "after recycling" refers to a sample that has undergone the fourth adsorption, desorption with anhydrous ethanol, washing with deionized water, and vacuum drying at 50°C for 24 hours. Figure 16 The XRD patterns of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 before and after recycling are shown. "Before recycling" refers to the fresh sample that has not been used for adsorption; "after recycling" refers to the sample after the fourth adsorption, anhydrous ethanol desorption, deionized water washing, and vacuum drying at 50°C for 24 hours. Figure 16 It can be seen that after recycling, some characteristic diffraction peaks related to HKUST-1 can still be detected in the sample, but the relative intensity, peak shape and background signal of some peaks have changed, indicating that the sample still retains some detectable crystal structure features after the fourth regeneration.

[0082] Combination Figure 15 It can be seen that the composite adsorbent material still has the ability to remove tetracycline hydrochloride after completing four adsorption and regeneration cycles. Figure 15 and Figure 16 These reflect the material's recyclability and the XRD changes before and after recycling, respectively.

[0083] Figure 17Infrared spectra of the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 before and after recycling. Figure 17 It can be seen that after recycling, the main absorption bands related to sodium alginate, PAN, and HKUST-1 can still be detected in the sample. However, the peak intensity, peak shape, and background signal of some absorption bands have changed, indicating that the relevant components and functional groups can still be detected after recycling, but their local chemical environment may have changed. Figure 16 It can be seen that after recycling, the sample still retains some detectable crystal structure features and main absorption bands.

[0084] Figure 18 This is a line graph showing the removal rate of tetracycline hydrochloride by the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 under dark and light conditions, with or without the addition of hydrogen peroxide.

[0085] The experimental group without hydrogen peroxide used an initial tetracycline hydrochloride aqueous solution with an initial concentration of 50 mg / L and an initial pH of 5.8; no pH adjustment was performed during the experiment. In the experimental group with hydrogen peroxide, 10 μL of a 30% (w / w) hydrogen peroxide aqueous solution was added to 20 mL of the above tetracycline hydrochloride aqueous solution. After mixing, the initial pH of the solution was measured to be 5.4; no pH adjustment was performed. The experimental group involving composite adsorbents subsequently added the composite adsorbent. Other experimental conditions for the dark state group were the same as those for the other groups. Figure 4 The other experimental conditions for the light group were the same as those for the light group. Figure 8 Same. By Figure 18 It can be seen that in Example 1, under dark conditions without the addition of hydrogen peroxide, the removal rate of tetracycline hydrochloride was 53.1% after 60 minutes and reached 83.5% after 360 minutes; under light conditions without the addition of hydrogen peroxide, the removal rate increased to 90.9% after 60 minutes and reached 94.5% after 360 minutes. Figures 5 to 7 The photothermal response test results show that the early tetracycline hydrochloride removal rate of the overall composite material of Example 1 is significantly improved under light conditions, but the existing results are not used to attribute this improvement entirely to the local photothermal effect of carbon black.

[0086] In the blank system where light and hydrogen peroxide coexisted but no composite adsorbent was added, the removal rates of tetracycline hydrochloride at 60 min and 360 min were 4.4% and 17.6%, respectively, indicating that under the experimental conditions, the light and hydrogen peroxide blank system contributed little to the removal of tetracycline hydrochloride. When Example 1 was combined with hydrogen peroxide, the removal rate reached 92.2% at 60 min and 99.0% at 360 min under dark conditions, significantly higher than the results of Example 1's dark adsorption alone. These results indicate that under the experimental conditions, the removal rate of tetracycline hydrochloride when Example 1 was combined with hydrogen peroxide was higher than that of Example 1's dark adsorption alone.

[0087] When light and hydrogen peroxide are present together, the removal rate of tetracycline hydrochloride in Example 1 is further improved, reaching 99.3% at 60 minutes and 99.8% at 360 minutes, both higher than that of Example 1 without hydrogen peroxide under the same light conditions. Compared with Example 1 and the hydrogen peroxide dark system, the removal rate under light conditions is increased by approximately 7.1 percentage points at 60 minutes, indicating that light conditions further improve the initial removal rate when Example 1 and hydrogen peroxide work together.

[0088] In summary, the overall removal rate of tetracycline hydrochloride was further improved when light, the composite adsorbent material, and hydrogen peroxide were present together. HKUST-1 and its copper-containing sites provided the interface for adsorption and oxidation reactions, while hydrogen peroxide participated in the Fenton-like catalytic oxidation process. The combined effect of these three factors resulted in the material exhibiting a synergistic removal effect of adsorption and Fenton-like catalytic oxidation under the conditions of light and hydrogen peroxide. Since all systems containing hydrogen peroxide had reached near-high removal rates after 360 min, the enhancing effect of light was mainly manifested in accelerating the initial removal rate.

[0089] The above results indicate that the SA / CB / HKUST-1 / PAN composite adsorbent material prepared in Example 1 not only has a high tetracycline hydrochloride removal rate, but also maintains the basic stability of the composite adsorbent layer and the HKUST-1 crystal structure after multiple cycles. This is because: PAN fibers provide macroscopic support, facilitating the overall recovery of the material; Cu² + The cross-linked sodium alginate gel layer immobilizes carbon black and provides an interface for the in-situ growth of HKUST-1, helping to reduce powder loss. Carbon black and HKUST-1 together improve the material's wettability, interfacial mass transfer, and accessibility of adsorption sites. Simultaneously, the addition of carbon black gives the material a stable photothermal response, and the overall composite material exhibits a relatively fast tetracycline hydrochloride removal rate under illumination. Existing results are not intended to attribute all performance improvements under illumination to the localized photothermal effect of carbon black. Therefore, the polyacrylonitrile fiber composite adsorbent material prepared in this invention combines rapid wetting, photothermal-assisted adsorption and removal, structural stability, convenient recovery, and reusability, making it suitable for the recycling treatment of antibiotic wastewater. Furthermore, Figure 18 The results showed that, under illumination, the experimental group with added hydrogen peroxide exhibited a faster initial removal rate and higher removal efficiency of tetracycline hydrochloride. This is because, under the coexistence of light and hydrogen peroxide, the copper-containing sites in the material may promote the participation of hydrogen peroxide in Fenton-like catalytic oxidation, and the adsorption enrichment and light-assisted oxidation may jointly affect the removal effect of tetracycline hydrochloride.

[0090] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A method for preparing a polyacrylonitrile fiber composite adsorbent material, characterized in that, Includes the following steps: Zinc oxide, carbon black, and sodium alginate were placed in water to obtain an SA / CB / ZnO aqueous dispersion. Polyacrylonitrile fibers were coated with SA / CB / ZnO aqueous dispersion, then transferred to copper nitrate aqueous solution for ionic crosslinking reaction, and then placed in pyromellitic acid solution to generate HKUST-1 in situ, thus obtaining polyacrylonitrile fiber composite adsorbent material.

2. The preparation method of the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, In the SA / CB / ZnO aqueous dispersion, the ratio of zinc oxide, carbon black, sodium alginate, and water is (0.2-0.48g):(0.4-0.72g):(1-1.8g):(50-60mL).

3. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, In the preparation of the copper nitrate aqueous solution, the concentration of copper nitrate trihydrate is 20.0-40.0 mg / mL, based on the volume of water used for solution preparation.

4. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, The preparation process of the pyromellitic acid solution The method includes the following steps: dissolving pyromellitic acid in ethanol, then adding N,N-dimethylformamide and water and mixing thoroughly; in the pyromellitic acid solution, the concentration of pyromellitic acid is 15.0-20.0 mg / mL, calculated by the sum of the volumes of the three solvents added: ethanol, N,N-dimethylformamide and water.

5. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, The specific process of the coating treatment includes the following steps: immersing polyacrylonitrile fibers in an SA / CB / ZnO aqueous dispersion for multiple consecutive immersions, with each immersion lasting 2-5 minutes, and obtaining SA / CB / ZnO / PAN coated fibers after immersion.

6. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, The specific process of the ionic crosslinking reaction includes the following steps: transferring the coated polyacrylonitrile fiber into a copper nitrate aqueous solution, immersing it at 25°C for 10-20 minutes to carry out the ionic crosslinking reaction, and then removing and cleaning it after the crosslinking is completed.

7. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, The specific process for generating HKUST-1 in situ The process includes the following steps: Polyacrylonitrile fibers that have undergone coating treatment and ion crosslinking reaction are placed in a pyromellitic acid solution and reacted at 25°C for 30-50 minutes to generate HKUST-1 in situ. After the reaction is completed, the fibers are removed, cleaned, and dried.

8. The method for preparing the polyacrylonitrile fiber composite adsorbent material according to claim 1, characterized in that, The ratio of the polyacrylonitrile fiber, SA / CB / ZnO aqueous dispersion, copper nitrate aqueous solution, and trimesic acid solution is 1g:(150-200mL):(150-200mL):(150-200mL).

9. A polyacrylonitrile fiber composite adsorbent material prepared by the preparation method of polyacrylonitrile fiber composite adsorbent material according to any one of claims 1-8.

10. The application of the polyacrylonitrile fiber composite adsorbent material as described in claim 9 in the treatment of antibiotic wastewater.

Citation Information

Patent Citations

  • Metal organic framework fiber material and preparation method thereof

    CN109876775A

  • HKUST-1 / alginate gel particle composite material as well as preparation method and application thereof

    CN115739046A